Effectiveness of the Jigsaw Technique in Improving Students' Reading Comprehension - Lilis Sumantri; Mukrim Mukrim; Mashuri Mashuri; Maf’ulah Maf’ulah (Journal of General Education and Humanities, 2026)
Reading comprehension constitutes a fundamental component of English language learning, as it enables students to construct meaning and understand written texts effectively. Nevertheless, many junior high school students continue to have difficulty comprehending English reading materials, especially when dealing with long descriptive texts and interpreting words with multiple meanings in different contexts. These difficulties often make students feel lazy and less motivated to read. Therefore, the Jigsaw technique was applied to encourage active learning, collaboration, and communication among students by dividing the learning materials into smaller sections, with each student responsible for studying and explaining their section to their peers. This study aimed to investigate whether the Jigsaw technique is effective in improving the reading comprehension of seventh-grade students at SMP Negeri 15 Palu, particularly in learning descriptive texts. This research employed a quasi-experimental design with two classes: VII A as the experimental group and VII C as the control group, totaling 60 students. A reading comprehension test consisting of 15 multiple-choice items and 5 essay questions was used as the research instrument. The data were analyzed using statistical procedures to determine whether the difference between the two groups was significant. The findings revealed that students taught using the Jigsaw technique demonstrated superior reading comprehension achievement compared to those taught through conventional methods. The statistical analysis showed that the obtained t value exceeded the critical value at the 0.05 level of significance, indicating that the alternative hypothesis was accepted. These results indicate that the Jigsaw technique, which promotes peer teaching, active participation, and cooperative learning, is an effective instructional strategy for enhancing students' reading comprehension and creating a more engaging learning environment.